Sargassum horneri as a Prebiotic Dietary Supplement for Immunity Development in Streptococcus parauberis Infected Zebrafish Model - Liyanage, Nisansala Madushani; Kim, Young-Sang; Nagahawatta, Dineth Pramuditha; Jin, Hwang; Yang, Hye-Won; Jayawardhana, Henarath Hetti Arachchilage Chathuri Kanchana; Jayawardena, Thilina U.; Jeon, You-Jin (Frontiers in Marine Science, 2022)
Sargassum horneri (SH) is a brown macroalgal species commonly found along the coast of Japan, China, and Korea. SH possesses valuable bioactive compounds that can be developed as functional food ingredients as well as pharmaceutical agents for both humans and animals. In this study, SH was tested for its potential prebiotic effect. Several solvent-assisted extracts of SH were tested on the growth of three species of probiotics (LAB) (Lactobacillus plantarum, Lactobacillus pentosus, Lactobacillus brevis) and fish pathogen bacteria (Streptococcus iniae, Streptococcus parauberis, Edwersiella tarda) both in vitro and in vivo. According to the in vitro results, Celluclast extract (SHC) and crude polysaccharide extract (SHCPs) of SH showed outstanding growth enhancing activity in all LAB species and excellent antibacterial activity against pathogenic bacteria dose-dependently. Both SHC and SHCPs induced the production of secondary metabolites from LAB. The secondary metabolites successfully reduced pathogenic bacterial growth. Furthermore, in vivo experiments revealed that co-treatment with LAB and SHC/SHCPs diminished the mortality of Streptococcus parauberis infected zebrafish by modulating iNOS, COX-2 expressions. Similarly, SH act as an anti-inflammatory agent against S. parauberis infection by hindering NF-κB pathway activation. Conclusively, the results achieved from the study suggest that S. horneri has the potential to be used as a prebiotic dietary supplement and possesses a protective effect against S. parauberis infections in the aquaculture industry.